The Influence of Social Media Content on The Interest of Gen Z Tourists to Visit Coban Lanang - Dhia, Fikhri Humam; Widodo, Teguh (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines the influence of social media marketing content on Generation Z tourists’ interest in visiting the Coban Lanang waterfall tourist destination in Batu City, East Java. Social media platforms, particularly Instagram and TikTok, are the primary sources of tourism information for Generation Z, making content quality a critical factor in shaping visit interest. Background Problems: Although Batu City has strong potential for natural tourism and supporting facilities, promotion through social media faces constraints due to limited human resources in digital content marketing. This condition raises questions about the effectiveness of existing social media content in attracting Generation Z tourists. Research Methods: A quantitative approach was employed using a saturated sampling technique. Data were collected through online questionnaires distributed to 50 visitors aged 18–26 who are active social media users and have been exposed to Coban Lanang-related content. Findings/Results:The results indicate that visual and informative social media content has a significant influence on increasing Generation Z tourists’ interest in visiting the destination. Conclusion: The study concludes that optimizing social media content quality is essential for local tourism managers to enhance Generation Z visit interest through effective digital marketing strategies.